Maternal Obesity and Risk of Postcesarean Wound Complications - Juliana Verticchio; Methodius G. Tuuli; Anthony Odibo; George A. Macones; Alison G. Cahill; Shayna N. Conner (2013)
Objective To estimate the effect of increasing severity of obesity on postcesarean wound complications and surgical characteristics. Study Design We performed a retrospective cohort study of consecutive cesarean deliveries at a tertiary care facility from 2004 to 2008. Four comparison groups were defined by body mass index (BMI; kg/cm2): < 30 (n = 728), 30 to 39.9 (n = 1,087), 40 to 49.9 (n = 428), or ≥50 (n = 201). The primary outcome was wound complication, defined as wound disruption or infection within 6 weeks postoperatively. Surgical characteristics were compared between groups including administration of preoperative antibiotics, type of skin incision, estimated blood loss (EBL), operative time, and type of skin closure. Results Of the 2,444 women with complete follow-up data, 266 (10.9%) developed a wound complication. Compared with nonobese women (6.6%), increasing BMI was associated with an increased risk of wound complications: BMI 30.0 to 39.9, 9.2%, adjusted odds ratio (aOR) 1.4 (95% confidence interval [CI] 0.99 to 2.0); BMI 40.0 to 49.9, 16.8%, aOR 2.6 (95% CI 1.7 to 3.8); BMI ≥50, 22.9%, aOR 3.0 (95% CI 1.9 to 4.9). Increasing BMI was also associated with increased rates of midline vertical incision, longer operative time, higher EBL, and lower rates of subcuticular skin closure. Conclusion A dose–response relationship exists between increasing BMI and risk of postcesarean wound complications. Increasing obesity also significantly influences operative outcomes.